SIDC Library - Marketing Information Services - Jesse, Lee Han Leng (PETRONAS, 2010)
Organized by PETRONAS in collaboration with Pustaka Sumber Ilmu, 15th – 17th May 2005 at Nikko Hotel Kuala Lumpur, Malaysia.